Socio-Cultural Practices and Entrepreneurial Behavior among the Tiv People in Benue State, Nigeria - mogbai, U; (Ph.D), Monica E.; ., Joseph; T., Terkula; Adudu, Adudu Chiangi (International Journal of Scientific Research and Management (IJSRM), 2017)
The study examines the Effect of Socio-cultural Practices on Entrepreneurial Behaviour in Benue State withemphasis among the Tiv people. Structured Questionnaire instrument with five likert scale was used for primarydata collection, a survey research method was adopted and a sample size of 400 respondents was used. Whilesecondary information were gathered from previous research studies done by different authors in journals, textbooksand internet among others. The data were analyzed using descriptive statistical tools such as tables and simplepercentage. Furthermore, multiple regressions were used for further analysis and test of hypotheses. The findingsfrom this study indicate that there was an established relationship between dimensions of socio-cultural practicesand entrepreneurial behaviour. The study revealed that most of socio-cultural factors have negative effect onentrepreneurial behaviour in Tivland, and Benue state at large. The study made some recommendations based on theresearch findings, some of which are; social groups, traditional and religious institutions should roll out policies andsensitization programmes that will help discourage cultural practices that are capable of retarding entrepreneurialbehaviour of people in Tivland such as high cost of funeral ceremonies, rather, promote the culture of investing suchfunds in small businesses. Family members in Tivland should always be involved in training their young onesthrough family businesses to let them have business background right from their childhood so as to give them initialorientation and encourage them on the need to be independent through generation of business ideas, venturecreation, purchases and sales of goods. This will help in boosting entrepreneurial behaviour and entrepreneurshipdevelopment in Tivland, Nigeria and the world at large.